The Influence of Flight Attendant Workload on Performance at Citilink Airlines in 2021 - Bata, Windi Trinova; Parman, Setyamartana (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
Services in the aviation world consist of three services: pre-flight, in-flight and post-flight services. In-flight services are carried out directly by the cabin crew, in this case the flight attendants, who are the parties tasked with providing direct services during the flight. In the world of flight attendants, there is a seniority system in carrying out tasks. The workload that must be done by junior flight attendants is greater than that of senior flight attendants. As a result, most junior flight attendants feel uncomfortable with the work environment caused by the lack of harmony between senior flight attendants and junior flight attendants. This study aims to determine the effect of flight attendant (FA) workload on their performance at Citilink Airlines in 2021. This study is a quantitative study, where data is collected by distributing questionnaires, observations and documentation to flight attendants at Citilink Airlines. The sample was carried out on 50 respondents using non-probability sampling techniques. Then the data was processed using simple linear regression analysis. The results of the study indicate that there is an influence of flight attendant workload on their performance at Citilink Airlines in 2021. Flight attendant workload affects their performance by 43.2%. While the remaining 56.8% of performance is influenced by other variables that are not studied and outside the concept in the researcher's research. The coefficient of determination ranging from 0.400-0.599 shows that flight attendant workload has a fairly strong influence on their performance at Citilink Airlines.